Interculturality in the Algerian University Context: Perceptions and Practices of French Language Teachers - Makhloufi , Mohammed; Ait Djida Mohand, Amokrane (El Omda in Linguistics and Discourse Analysis, 2022)
This article first discusses the place of the intercultural dimension in the Algerian university context. It then provides an overview of the stages that led to the emergence of the concept of interculturality in the didactics of French as a Foreign Language (FLE), its definitions, and the importance of intercultural competence in communication. Next, through a field survey conducted in 2018 among French language teachers at the Department of French Language and Culture at the University of Mohamed Boudiaf of M’sila, the study presents some findings regarding teachers’ perceptions of interculturality, their training in intercultural didactics, and their pedagogical practices in the classroom.